Textural Characteristics of Coastal Sediments Between Bhavanapadu and Baruva Villages in Srikakulam District, East Coast of India - Rao, T. Sankara; Reddy, K. Satyanarayana; Swathi, G.; Sekhar, Ch. Ravi; Kumar, B. Anantha; Satyanarayananaidu, K.; Saheb, Shaik John; Ramakrishna, B.; Sreedhar , P. (International Journal of Membrane Science and Technology, 2023)
The texture of a rock or sediment is the size, shape, and arrangement of the grains. The microgeometry of sediments deals with intergranular relationship of grains, their size and shape. In the present study, a total of sixty surficial sediment samples were collected from the study area (foreshore-20, berm-7, backshore-13, and dunes-20) with an interval of 1 km. The geology, geomorphology, drainage pattern, climate, waves, and currents are discussed. The grain size parameters viz., mean grain size, standard deviation, skewness, and kurtosis are discussed extensively. Sand is the predominant component in all the sediment samples (99.82–99.93%) whereas silt and clay contents are less than 1% from the four environments. The mean grain size of the sediment samples shows that medium grained sands are followed by fine grained sands indicating a low energy environment of deposition. The standard deviation values reveal that the sediments are well to moderately sorted. The average values of skewness indicate that all the sediment samples are negatively skewed to positively skewed representing an environment of deposition of low to moderate energy conditions. Most of the kurtosis values indicate that the sediments are of platykurtic to leptokurtic in nature. The platykurtic nature of sediments indicates the sorting of tail portions of sediment populations.